Kepuasan Konsumen Berbasis Harga, Kepercayaan Konsumen dan Promosi - Yulianingsih, Yulianingsih; Ismartaya, Ismartaya; Amelia S, Vera (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine the influence of price, consumer trust, and promotion on consumer satisfaction at CV. Syifa Adventure. The research sample was 100 respondents using a non-probability sampling technique or approach using accidental sampling technique. The type of research is descriptive and verification using multiple linear regression analysis methods. The results indicate that consumer responses regarding price fall into the moderately agreeable category, with price affordability as the highest-rated indicator and price-quality conformity as the lowest. Consumer trust is rated as agreeable, with openness as the highest-rated indicator and integrity as the lowest. Promotion is rated as agreeable, with sales promotion as the highest-rated indicator and advertising as the lowest. Overall, consumer satisfaction is categorized as satisfactory, with willingness to recommend as the highest-rated indicator and interest in revisiting as the lowest. The F-test results show that price, consumer trust, and promotion simultaneously have a positive and significant influence on consumer satisfaction. The t-test results indicate that price and promotion individually have a positive and significant effect on consumer satisfaction, while consumer trust does not have a significant impact. These findings suggest that improving appropriate pricing and effective promotion can enhance consumer satisfaction at CV. Syifa Adventure, while consumer trust needs improvement in integrity to achieve a more significant impact.